1977
DOI: 10.1159/000241037
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Serum Thyrotropin (TSH) of Suckling Rats after Thyroliberin (TRH) Injection to Lactating Mothers

Abstract: Injection of 50 μg TRH to lactating rats 15 days after parturition was followed 4h after treatment by an increase of serum TSH and a decrease of absolute and relative pituitary TSH content in suckling pups when compared to sucklings of saline-treated mothers. The weight of the pituitary and thyroid also decreased. Results indicate that TRH administered to lactating rats induces release of TSH from the pituitary of suckling pups. An increase of the variability of serum TSH and a decrease of pituitary TSH conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…According to Amarant et al (45), the concentration of TRH in milk exceeds that in serum. Their suggestion that milk might be a source of TRH in suckling rats is supported by (a) limited decrease of TRH serum levels and presence of TRH in the upper gastrointestinal tract of suckling rats after pancreatectomy (50); (b) the disappearance of contractile response to TRH in the duodenum of suckling rats after weaning whereas continuation of suckling can prevent its disappearance (51); and (c) interesting studies of the Bratislava group (52). They have shown that injection of TRH (50 p.g) to lactating rats 15 days after parturition is followed shortly (4 h) by an increase of serum thyroid-stimulating hormone (TSH) and a decrease of pituitary content in suckling rats when compared to sucklings of saline-treated mothers.…”
Section: Thyrotropin-releasing Hormone (Trh)mentioning
confidence: 99%
“…According to Amarant et al (45), the concentration of TRH in milk exceeds that in serum. Their suggestion that milk might be a source of TRH in suckling rats is supported by (a) limited decrease of TRH serum levels and presence of TRH in the upper gastrointestinal tract of suckling rats after pancreatectomy (50); (b) the disappearance of contractile response to TRH in the duodenum of suckling rats after weaning whereas continuation of suckling can prevent its disappearance (51); and (c) interesting studies of the Bratislava group (52). They have shown that injection of TRH (50 p.g) to lactating rats 15 days after parturition is followed shortly (4 h) by an increase of serum thyroid-stimulating hormone (TSH) and a decrease of pituitary content in suckling rats when compared to sucklings of saline-treated mothers.…”
Section: Thyrotropin-releasing Hormone (Trh)mentioning
confidence: 99%